1990
DOI: 10.1203/00006450-199005000-00014
|View full text |Cite
|
Sign up to set email alerts
|

Insulin-Like Growth Factor-I Gene Analysis in Subjects with Constitutionally Variant Stature

Abstract: ABSTRACT. The IGF-I gene from leukocyte DNA of a control population of normal stature was studied using Southern blotting. Restriction fragment lengths for 21 enzymes were determined and three restriction fragment length polymorphisms (RFLP) were found (EcoRV, HindIII, and PvuII). In addition, the IGF-I gene of 64 constitutionally short subjects, five Pygmies, and 10 constitutionally tall subjects was analyzed. No IGF-I gene alterations were detectable by Southern blot in any of these conditions. Linkage analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0
1

Year Published

1991
1991
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 11 publications
1
8
0
1
Order By: Relevance
“…As in previous studies, 20,21,55 we could find no polymorphism in the 5 0 region of the IGF1 gene associated with stature among Central African pygmies and non-pygmies. As a recombination hotspot separates most of the IGF1 gene from its 5 0 region (see the recombination rate estimated from HapMap Phase 2 56 in Supplementary Figure S1), we re-sequenced other portions of this gene and found that a SNP (rs11831436) in the second intron presented an outlying value of the genetic distance between the Baka pygmies and the Nzimé non-pygmies.…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…As in previous studies, 20,21,55 we could find no polymorphism in the 5 0 region of the IGF1 gene associated with stature among Central African pygmies and non-pygmies. As a recombination hotspot separates most of the IGF1 gene from its 5 0 region (see the recombination rate estimated from HapMap Phase 2 56 in Supplementary Figure S1), we re-sequenced other portions of this gene and found that a SNP (rs11831436) in the second intron presented an outlying value of the genetic distance between the Baka pygmies and the Nzimé non-pygmies.…”
Section: Discussionsupporting
confidence: 74%
“…Most of the primers were designed using Primer 3 26 and others were adapted from previous studies. 21,27,28 Primer sequences can be found in Supplementary Table S1. Amplifications were performed using standard PCR conditions (available upon request).…”
Section: Amplification and Analysis Of The Sequencesmentioning
confidence: 99%
See 1 more Smart Citation
“…Common polymorphisms in GH1 (Hasegawa et al 2000;Millar et al 2003) and IGF1 Schneid et al 1990;Vaessen et al 2001) have been associated with height variation. However, these initial association Wndings have not been validated in other replication populations and they were identiWed in relatively small cohorts, lowering the likelihood that these represent robust associations (Ioannidis et al 2003;Lohmueller et al 2003;Wacholder et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…In one of the studies, a significantly decreased prevalence of one allele of an EcoRV RFLP associated with the IGF-I gene was found in children with CSS (12), and it was suggested that this might indicate a role for minor abnormalities of the IGF-I gene in CSS.…”
mentioning
confidence: 99%